Tips and Tricks for the Trauma Patient - Goei, Anthony D. (Thieme Medical Publishers, 2010)
Interventions on the trauma patient are an essential component of the complete scope of care that is provided to the multiply injured patient today. The active participation by the interventional radiologist along the entire spectrum of clinical care is very important to optimize patient outcomes. Suggestions on how to establish a clinical presence are presented. A few of the newer concepts and terminology applicable to trauma care are reviewed. Tips useful in the trauma room, in the interventional radiology suite, and during the postprocedural period are discussed.